Pembuatan Bakso Ikan Dengan Proporsi Ikan Tuna (Thunnus Sp) Dan Ebi Dengan Penambahan Puree Semanggi (Marsilea Crenata) - Muhammad Fikri Bachruddin Patty; Any Sutiadiningsih; Niken Purwidiani; Mauren Gita Miranti (Pusat Riset dan Inovasi Nasional, 2023)
This research is about fish meatballs using the main raw material of tuna which is proportioned with shrimp to help give more taste and be able to increase the nutritional quality content of the product and the addition of clover puree is expected to be able to increase the nutritional content and also be able to increase the potential for rare local ingredients. used. The purpose of this study was to determine 1) the sensory quality of fish balls with the proportion of tuna and shrimp and the addition of cloverleaf puree 2) the nutritional and non-nutritional content based on laboratory tests including protein, carbohydrates, fat, water, ash, calcium and potassium 3) cost raw material for fish balls. This type of research is an experiment. Observation data collection techniques by means of sensory quality tests were carried out by 35 panelists. The independent variables in the study were the proportions of tuna and shrimp (80%:20%), (70%:30%) and 60%:40%) and clover puree (5% and 10%). The dependent variable of the research is sensory quality including shape, color, texture, elasticity, aroma, and taste. The control variables in this study include the types of materials, equipment and processing techniques. Data analysis used double anova test and Duncan's further test. The results showed 1) there was an effect on the sensory quality of making fish balls with the proportion of tuna and shrimp with the addition of cloverleaf puree including color, aroma and taste. 2) there is no effect on the sensory quality of shape, texture, and elasticity of the meatballs. 3) the selected product contains nutrition equal to or greater according to SNI 2017 including protein content 8.11%/100gr, fat 3.86%/100gr, water 36.58%/100gr, carbohydrates 49.88%/100gr, ash 1 .24%/100gr, calcium 75.80 mg/100 gr, potassium 86.90 mg/100 gr 4) the best product has a raw material cost of IDR 56,450.